Holdaway soft tissue cephalometric standard for Malay adults / Indah Yuri Noviaranny, Nurqasteena Kamarol Hissam and Puteri Ummi Atilia Abu Bakar - Noviaranny, Indah Yuri; Kamarol Hissam, Nurqasteena; Abu Bakar, Puteri Ummi Atilia (Faculty of Dentistry, Universiti Teknologi MARA, 2022)
Objectives: The aim of this study were: 1. To report facial soft tissue measurements in Class I Malay adult, 2. To compare between gender, 3. And to check applicability of Holdaway values for Class I Malay adults. Materials and Methods: Lateral cephalometric of 20 men and 20 women age 20-30 years with Class I skeletal was selected from Orthodontic Clinic, Faculty of Dentistry UiTM. The subject has no orthodontic or orthognathic surgery done before the radiograph was taken. The radiograph was traced and evaluated by the authors. Cephalometric landmarks were located according to Holdaway analysis. Ten linear and two angular measurements were produced on each radiograph and measured. For each variable, the mean and standard deviation (SD) was calculated using simple t-test (p<0.05). Results: Soft tissue measurements for Malay have significant difference as compared to Holdaway value except for three parameters which are soft tissue facial angle, superior sulcus depth, and soft tissue chin thickness. When compared between genders, male has larger value in skeletal profile convexity, upper lip strain and soft tissue thickness while females demonstrated higher value in nose prominence and superior sulcus depth. Conclusions: It has been concluded that Malay values for Holdaway soft tissue analysis were found to be statistically different. Hence Holdaway soft tissue values are not applicable for use in orthodontic practice for Malay population. Further research to confirm values obtained for Malay population would aid in better diagnosis and treatment planning.